Bildung und Briefe im 6. Jahrhundert Studien zum Mailänder Diakon Magnus Felix Ennodius - Schröder, Bianca-Jeanette (Millennium-Studien / Millennium Studies, 2011)
Ennodius lived during the reign of the Ostrogothic King Theoderic. When he wrote his various works he was deacon in Milan, later becoming Bishop of Pavia. This study is an introduction to his life and works, and reveals how the deacon promoted the ´worldly` culture of languages and rhetoric. Particular attention is paid to the letters which he sent to secular and ecclesiastic officials (including the Pope), as well as relatives. Among other things, he demanded that the Roman ruling classes crown their privileged position by dedicating themselves to cultural matters.